2020
DOI: 10.26911/thejhpb.2020.05.01.02
|View full text |Cite
|
Sign up to set email alerts
|

The Effectivity of Nutrition Education Booklet on Knowledge, Fast-food Consumption, Calorie Intake, and Body Mass Index in Adolescents

Abstract: Background:The prevalence of adolescent obesity is increasing worldwide with proportions varying from country to country or between geographical regions within a country. The purpose of this study was to determine the effect of nutrition education with booklet media on knowledge, fast food consumption, calorie intake, and body mass index (BMI) in adolescents. Subjects and Method: This was a quasy experiment with no control group. The study was conducted in Junior high school in Medan, North Sumatera. A sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…Media booklets and counseling are useful in conveying information and making it easier for someone to understand information that is considered unknown or considered complicated [30]. A study showed that booklets were effective for increasing knowledge as well as changing one's behavior to reduce consumption of fast food and high-calorie and fat foods [31]. In line with this study, there was a significant difference in nutrition education using booklets and counseling on home food availability in the intervention group, which experienced an increase in providing healthy food at home (fruits and vegetables).…”
Section: The Effect Of Nutrition Education With and Without Booklet M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Media booklets and counseling are useful in conveying information and making it easier for someone to understand information that is considered unknown or considered complicated [30]. A study showed that booklets were effective for increasing knowledge as well as changing one's behavior to reduce consumption of fast food and high-calorie and fat foods [31]. In line with this study, there was a significant difference in nutrition education using booklets and counseling on home food availability in the intervention group, which experienced an increase in providing healthy food at home (fruits and vegetables).…”
Section: The Effect Of Nutrition Education With and Without Booklet M...mentioning
confidence: 99%
“…In addition, the booklet delivered a message in the form of a book with a combination of narration and pictures so that the information contained is more complete, more detailed, clear, and educative [30], [31]. While nutrition counseling is a two-way communication process between counselor and client to help identify and solve client problems, aiming to assist in behavioral change related to nutrition, to increase the person's health status.…”
Section: Introductionmentioning
confidence: 99%
“…Someone will be motivated to do something if the social environment they are located in has a positive opinion on the behavior (p2ptm.kemkes, 2018). Previous research stated that statistically, peer education significantly affects attitudes about nutrition and obesity and reduces fast food consumption habits (Said I, Hadi AJ, Manggabarani S, Tampubolon IL, Maryanti E, 2020).…”
Section: Public Relations Functions To Change Attitudes and Actionsmentioning
confidence: 99%
“…Health administrators also need to master various methods and utilize a variety of technologybased multi-media to facilitate the delivery of varied programs. Nutrition education through booklet media in specific communities has an effect on increasing knowledge, reducing consumption of fast foods, calorie intake, and body mass index (BMI) in adolescents (Said I, Hadi AJ, Manggabarani S, Tampubolon IL, Maryanti E, 2020).…”
Section: Public Relations Functions To Change Attitudes and Actionsmentioning
confidence: 99%
“…Hasil penelitian sebelumnya juga menyebutkan bahwa melalui edukasi mengenai gizi seimbang telah terjadi peningkatan pengetahuan ibu mengenai gizi seimbang pada balita. Meningkatnya pengetahuan mengenai gizi seimbang dan pengolahan makanan boleh jadi akan diikuti dengan perubahan perilaku (Kameliawati et al, 2019).Penelitian Said , 2020 juga senada menyebutkan efektivitas booklet dalam meningkatan pnegetahuan gizi dan mengurangi asupan fast food pada remaja (Said et al, 2020).…”
Section: Hygiene Dan Sanitasi Makananunclassified